Adverse reactions to antiretrovirals presented by HIV patients: a scientific (Research, Society and Development, 2021)
HIV patients start their treatments in the Unified Health System (SUS) through the Family Health Strategy Assistance (ESF) and this, in turn, coordinates all care provided and the referral of the patient to a reference unit for counseling, monitoring and control of infection in an integral and resolutive way. However, we hope that this work will contribute to understanding the types of adverse reactions that have occurred by users of HIV medications. All publications that have data on pharmacological treatments for HIV were used, from a certain date (2019-2020). Data were collected using the scientific databases: Latin American and Caribbean Literature in Health Sciences (LILACS), National Library of medicine (PUBMED), PERIODICOS, SCIENCE DIRECT, Virtual Health Library ( VHL), Scientific Electronic Library Online (SCIELO) and Cochrane Library; and the technological bases: World Intellectual Property Organization (WIPO) and National Institute of Industrial Property (INPI). We use AS DEScriptors: ADVERSE REACTIONS TO ANTIRETROVIRAL DRUGS, ADVERSE REACTIONS TO ANTIRETROVIRAL DRUGS IN PREGNANT WOMEN and ANTIRETRORETROVIRAL.  The publishing language was in Portuguese, English and Spanish, attending a historical series of at least five years. A number of articles were observed on the scientific database. This treatment of the virus does not cure because of the persistent accumulation of latentemente infected cells. Even with mild symptoms, they can lead to a decrease in the quality of life of the carrier, thus necessary more research on the subject. We must remember that their quality of life directly impacts our society and therefore matters to everyone.